EFFECT OF PERCEIVED USEFULNESS, PERCEIVED EASE OF USE AND TRUST TOWARDS OVO CUSTOMER LOYALTY (A Study on the Customers of OVO in Malang) - Heryndra, M. Gifhari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
The development of information and communication technology, especially in application systems and social media, has led to a variety of new creative industries, one of which is in the field of payment services. The use of OVO applications is based on the Technology Acceptance Model (TAM) theory that was introduced by Davis in 1989. TAM shows the usefulness and ease of use will affect the informants' individual intentions in using techniques. This study aimed to examine the influence of Perceived Usefulness empirically, perceived Ease of use and trust towards Customer loyalty in OVO applications (the study of OVO users in Malang). This is a quantitative study, the source of the data used in this study is primary data that is the source of data in the form of objects, things, or people where the researcher observes, reads and asks questions about the data that will later be used for hypothesis testing using SPSS For data collection methods, spreading An online questionnaire was used in this study with a 5-point Likert Scale. Criteria for respondents in research residing in Malang, using the application of their own volition, and using the application at least three times a month. Samples were taken as many as 100 respondents from OVO users in Malang. Data analysis in this study used Multiple Linear Regression Analysis and hypothesis testing using t-test processed with SPSS software ver. 20. In other words, this study used non probability sampling and accidental sampling techniques. The results showed a positive influence towards Perceived Usefulness, Perceived ease of use (ease of use), and trust in customer loyalty.Keywords: Perceived Usefulness, Perceived Ease of use, Trust, Customer Loyalty